The Effect of a Pre-Arraignment Legal Representation Pilot on Pretrial Release and Criminal Case Outcomes - Lacoe, Johanna (Journal of quantitative criminology, 2025)
ObjectivesLow-income individuals facing criminal charges experience disproportionately high rates of pretrial detention and conviction. We study a pilot program in Santa Clara County, CA that aims to address this inequity by providing access to public defenders immediately following arrest.MethodsThe Santa Clara Public Defender agreed to provide pilot services one day per week, rotating the intervention day across weeks. Individuals booked on an intervention day were eligible for early legal representation, while individuals booked on control days received public defender services as usual. The study leverages the rotating treatment day to compare pretrial release and case outcomes between eligible individuals booked on treatment days and eligible individuals booked on control days.ResultsPilot program participants were 28 percentage points more likely to secure pretrial release, and 36 percentage points more likely to see their cases dismissed, relative to comparable individuals who generally first meet with their public defender at arraignment.ConclusionsProviding prompt access to legal representation could improve release and case outcomes for low-income individuals and the efficacy of public defense.